Chalcogenide Science in Romania. Issue 11 (24th September 2020) - Lőrinczi, Adam; Bădică, Petre; Boţilă, Toni; Ciurea, Magdalena; Velea, Alin; Popescu, Aurelian; Socol, Gabriel; Antohe, Stefan; Nedelcu, Nicoleta; Sobeţkii, Arcadie
Abstract : Almost six decades ago, in Romania a small group of physicists begun to study chalcogenide compositions, motivated primarily by the desire to understand the phase‐change phenomenon in these materials, discovered recently, at that time, by Stanford R. Ovshinsky. It took not too long for them to realize the challenges these materials set to the research. With newcomers to the field, the research was broadened. In some cases just for basic research, to model, and to understand the chalcogenide materials, whereas in other cases, the applicative potential was revealed and used. Herein, the evolution of the field of these somewhat exotic materials is followed, listing the main contributions done in Romania, both in basic and applied research. Abstract : Almost six decades ago, in Romania some physicists begun to study chalcogenide compositions, motivated by the desire to understand the phase‐change phenomenon in these materials, discovered recently, at that time, by Stanford R. Ovshinsky. Herein, the evolution of the field of these exotic materials is shown, listing the main contibutions done in Romania, both in basic and applied research.